From Enterprise Architecture to IT Governance Elements of Effective IT Management - Niemann, Klaus D.; SpringerLink (Online service) (Wiesbaden : Vieweg, 2006)
This book shows its readers how to achieve the goal of genuine IT governance. The key here is the successful development of enterprise architecture as the necessary foundation. With its capacity to span and integrate business procedures, IT applications and IT infrastructure, enterprise architecture opens these areas up to analysis and makes them rich sources of critical data. Enterprise architecture thereby rises to the status of a crucial management information system for the CIO. The focused analysis of the architecture (its current and future states) illuminates the path to concrete IT development planning and the cost-effective and beneficial deployment of IT. Profit from the author's firsthand experience - proven approaches firmly based in enterprise reality.
Introduction: When Things Just Work -- Foundations: Finding the Starting Point -- Goals: Doing the Right Things Right -- Documentation: Structuring Enterprise Architecture -- Analysis: Evaluating Enterprise Architecture -- Planning: Creating Enterprise Architecture -- Implementation: Developing Enterprise Architecture -- Safeguarding: Controlling Enterprise Architecture Development -- Conclusion: Finding the Right Course.
Keywords: Business; Information technology; Business -- Data processing; Management information systems; Computer science; Business and Management; IT in Business; Management of Computing and Information Systems; Information Systems Applications (incl. Internet).; Electronic books